1987
DOI: 10.1210/jcem-64-6-1241
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism in Children Treated with Long Term Medical Therapy: Twenty-Five Percent Remission Every Two Years*

Abstract: We use an antithyroid drug for the treatment of hyperthyroidism due to Graves' disease in children and adolescents for as long as the patients are willing to comply and/or tolerate the drug. In more than 60 patients treated since 1961, the remission rate was 25% in the first 2 yr. This report looks at these same patients again, followed for an additional 5 yr. Survival analysis methods applied to the follow-up data on 63 children confirm our original statistical findings and suggest a continuing remission rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
102
1
5

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 0 publications
6
102
1
5
Order By: Relevance
“…The risk of new hyperthyroidism was considerably higher in patients who were TRAbpositive at the end of medical therapy, but the initial TRAb values and the fall in TRAb during therapy overlapped between patients who became hyperthyroid and those who remained euthyroid. In patients who do not accept the risk of new hyperthyroidism after the stop of medication, prolonged medical therapy may be useful (28)(29)(30)(31). This should be balanced against the risk of drug side effects (32).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of new hyperthyroidism was considerably higher in patients who were TRAbpositive at the end of medical therapy, but the initial TRAb values and the fall in TRAb during therapy overlapped between patients who became hyperthyroid and those who remained euthyroid. In patients who do not accept the risk of new hyperthyroidism after the stop of medication, prolonged medical therapy may be useful (28)(29)(30)(31). This should be balanced against the risk of drug side effects (32).…”
Section: Discussionmentioning
confidence: 99%
“…Based on published reports describing outcomes for children treated with antithyroid medications for Graves' disease, up to 10 years ago, PTU was more widely used than MMI [1113]. More recent data however, suggest that two thirds of children in the United States treated with antithyroid medications are now being treated with MMI, and one-third are treated with PTU [4].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the risk of side effects, the lowest possible dose of the drug should be used. Several investigators have reported that such therapy may prevent relapse of overt Graves' disease (17)(18)(19)(20). One mechanism behind such a protective effect of low dose MMI therapy may be a decrease in the risk of reactivation of the vicious cycle illustrated in Figure 2.…”
mentioning
confidence: 99%